Rose Harbor in bloom : a novel - Macomber, Debbie (Macomber, Debbie. Rose Harbor Inn., 2013)
In Cedar Cove three women -- innkeeper Jo Marie Rose, young Annie Newton, and high-powered businesswoman Mary Smith -- make peace with their pasts as they boldly welcome their futures.